Deep sedation predicts pressure injury in patients admitted to intensive care units. Issue 6 (19th January 2022) - Sasabe, Yayoi; Niitani, Mayumi; Teramoto, Chie; Yamaga, Satoshi; Shime, Nobuaki; Tanabe, Kazuaki; Kataoka, Tsuyoshi; Sawatari, Hiroyuki
Abstract: Background: Patients in intensive care units (ICU) are frequently prescribed sedatives, which might increase the risk for pressure injury (PI). Although the association between sedation and incidence of PI has been noted, the adequate sedation level to prevent the incidence of PI in patients admitted to ICU is still unclear. Aim: This study aimed to investigate the association between fluctuating sedation levels and the incidence of PI in patients admitted to ICU. Study Design: We retrospectively reviewed the medical records of 104 patients admitted to ICU. Data regarding the length of ICU stay (LOS) and comorbid infection were abstracted from medical records. The Richmond Agitation‐Sedation Scale (RASS) was scored twice per day, and the standardized RASS (S‐RASS, summation of RASS values divided by the number of samples) was used to evaluate changes in sedation levels. Results: Among the 104 included patients, 65 patients (62.5%) were male (median age: 68.0 years), and 13 patients (12.5%) had PI during ICU admission. S‐RASS scores were lower in patients with PI than in those without PI ( P = .0001) even after adjustment for confounders (OR [95%CI]: 0.14 [0.03–0.58], P = .006). The LOS and infections were higher in patients with PI than in those without PI ( P < .0001 and P = .005, respectively). The cut‐off value of S‐RASS for PI incidence was −3.2 (sensitivity: 88%; specificity: 85%), and a significant predictor of PI incidence (HR [95%CI]: 20.07 [2.53–159.11], P = .005). Conclusions: Deeper sedation levels based on S‐RASS scores, which account for the effects of fluctuating sedation levels, were a strong, highly accurate predictor of PI incidence in patients admitted to ICU. Relevance to Clinical Practice: Assessing fluctuations in the level of sedation using the S‐RASS might help to identify sedative‐induced PI in patients admitted to ICU.